Partial Characterization of Chitosanase from Bacillus cereus Strain BFE5400 Isolated from Snakehead Fish Intestine - Shanti Dwita Lestari; Ace Baehaki; Guttifera Guttifera (Universitas Gadjah Mada, 2020)
Feeding pattern of wild snakehead fish (Channa striata) which includes shrimp and small crustaceans makes it is intestine a good source of chitinase and chitosanase enzymes. This study aimed to isolate chitosanase producing bacteria from snakehead fish intestine, to select isolate with highest chitosanolytic activity, to produce chitosanase using the selected isolate and partially characterize the resulting enzyme. I2 isolate exhibited the highest chitosanolytic index with the value of 1.5 and produced enzyme with an activity of 0.00331 U/mL after 72 hours incubation. The ultimate bacterial density was at the 24th hour with a turbidity value of 0.5315. The enzyme activity was optimum at pH 6, with a value of 0.00816 U/mL, while the optimum temperature was 70°C with the enzyme activity of 0.00785 U/mL. Genetic identification of I2 isolate using 16S rRNA showed that the isolate has a high similarity to Bacillus cereus strain BFE 5400.